Correlation Between Knowledge, Academic Stress, and Gastritis Prevention Among Students at STIKes Papua Sorong - Fitriani, Fitriani; Hardiyanti, Rina; Tyas, Lusia Wahyuning; Sokametan, Julita Cintya Sari; Sukmana, Mayusef (Fakultas Kedokteran, 2026)
According to data from the World Health Organization (WHO) in 2020, the prevalence of gastritis in Indonesia reached 40.8%. Gastritis cases remain notably high in several regions, affecting 274,396 individuals out of a total population of 238,452,952. Based on data from the Indonesian Ministry of Health (Kemenkes RI) in 2020, the reported prevalence of gastritis was 31.2% in Surabaya, 46% in Denpasar, 50% in Jakarta, 32.5% in Bandung, 35% in Palembang, and 31.7% in Aceh.The aim of this study was to determine the relationship between knowledge and academic stress with gastritis prevention among students at STIKES Papua, Sorong City.This research employed a quantitative approach with a cross-sectional design. The study population consisted of all active second-semester students enrolled at STIKES Papua, Sorong City. A simple random sampling technique was used to select 151 respondents. The study was conducted in July 2024. Data were collected using a validated questionnaire, and the results were analyzed using the chi-square test.The findings revealed a p-value of 0.017 for the variable of knowledge, which is less than the significance level (α = 0.05), indicating a significant relationship between students' knowledge and gastritis prevention. Meanwhile, the p-value for academic stress was 0.112, which is greater than α = 0.05, indicating no significant relationship between academic stress and gastritis prevention.In conclusion, there is a statistically significant relationship between knowledge and gastritis prevention among second-semester students at STIKES Papua, Sorong City. However, no significant relationship was found between academic stress and gastritis prevention. It is recommended that the institution's administrators and lecturers increase health education efforts, particularly in promoting effective gastritis prevention strategies among students